EFFORTS TO INCREASE LEARNING OUTCOMES THROUGH THE KANGURU JUMP PLAYING APPROACH IN CLASS V STUDENTS - Eko Putut Dumiyanto (Yayasan Citra Dharma Cindekia, 2021)
The purpose of this research is to increase the effectiveness of student learning and optimize the use of teaching aids as facilities and infrastructure in the subjects of Physical Education, Sports and Health. The research subjects were 21 students consisting of 13 male students and 8 female students in fifth grade at SD Negeri Karangwinongan, Mojoagung District, Jombang Regency for the 2019/2020 school year. This research will be carried out using two cycles and 4 meetings. The data collection technique that the author uses is in the form of tests and non-tests. The implementation of improving student learning activities went quite well. The results of the first cycle at the first meeting the average value was 1.90 and at the second meeting the average value was 2.71. While the results of the second cycle at the first meeting the average value was 3.38 and at the second meeting the average value was 3.66, each meeting experienced a fairly good increase. The results of the learning test the average value obtained in the evaluation of student learning improvements in the first cycle was 72 with 5 students who had not completed while those who completed were 16 students out of 21 students. While the average value obtained in the implementation of the improvement of learning cycle II is 75 and 20 students have achieved completeness and 1 student is not complete.